Structuring Labour Migration in Rural Nepal: A Case of Babiyabirta VDC, Morang, Nepal - Gurung, Yogendra B. (Economic Journal of Nepal, 2012)
Labour migration has been a patterned behavior in Nepal. It has tremendous implication on country’s social and economic development. In this regard, this paper tries to identify structure of labour migration from rural Nepal based on data obtained from a micro-level sample survey conducted in 2009. The survey collected both quantitative and qualitative information. Findings suggest that migration is a result of an interactive function of multilevel social structures –individual, household and community structures or a larger society. The social structure plays a role of social networks by sharing experiences and information and facilitating potential migrants in the society. Household accumulates knowledge about migration through the interaction with community people and larger society and interact with family members. Finally, household takes decision whether and who (household member) to involve in migration.Out-migration is pervasive among individuals that are able bodied, literate, and even educated males and they mostly belong to hill origin. Most of them are from household with land but size of land is small so about 77 percent families are facing the problem of food insufficiency. Regarding community and larger social structure, there are about a dozen of formal social and development organizations currently active in Babiyabirta. Access to these organizations is relatively better among migrant’s households. Friends, relatives, neighbors, recruitment agencies, and agents are the main actors among the social networks. It is instrumental to connect villagers with foreign labour migration by channeling the migration process at three levels – origin, other intermediate cities, Kathmandu, and destination. They provide knowledge about migration, financial support, and help in the process. The Economic Journal of Nepal, Vol. 35, No. 1, January-March 2012 (Issue N0. 137)